Selection of reference genes for qRT-PCR examination of wild populations of Atlantic cod Gadus morhua - Lie Kai K; Søfteland Liv; Olsvik Pål A (BMC Research Notes, 2008)
Abstract Background Extensive sequencing efforts have been taking place for the Atlantic cod (Gadus morhua) in recent years, the number of ESTs in the Genbank has reached more than 140.000. Despite its importance in North Atlantic fisheries and potential use in aquaculture, relatively few gene expression examination exists for this species, and systematic evaluations of reference gene stability in quantitative real-time RT-PCR (qRT-PCR) studies are lacking. Results The stability of 10 potential reference genes was examined in six tissues of Atlantic cod obtained from four populations, to determine the most suitable genes to be used in qRT-PCR analyses. Relative transcription levels of genes encoding β-actin (ACTB), elongation factor 1A (EF1A), actin-related protein-2 (ARP-2), glyceraldehyde-3P-dehydrogenase (GAPDH), ubiquitin (Ubi), acidic ribosomal protein (ARP), ribosomal protein S9 (S9), ribosomal protein L4 (RPL4), RPL22 and RPL37 were quantified in gills, brain, liver, head kidney, muscle and middle intestine in six juvenile fish from three wild populations and from farmed Atlantic cod. Reference gene stability was investigated using the geNorm and NormFinder tools. Based on calculations performed with the geNorm, which determines the most stable genes from a set of tested genes in a given cDNA sample, ARP, Ubi, S9 and RPL37 were among the most stable genes in all tissues. When the same calculations were done with NormFinder, the same genes plus RPL4 and EF1A were ranked as the preferable genes. Conclusion Overall, this work suggests that the Ubi and ARP can be useful as reference genes in qRT-PCR examination of gene expression studying wild populations of Atlantic cod.